Cardiac cachexia: the mandate to increase clinician awareness. Issue 4 (December 2019) - Lena, Alessia; Ebner, Nicole; Coats, Andrew J.S.; Anker, Markus S.
Abstract : Purpose of review: Heart failure is a frequent problem in an ageing population, associated with high rates of morbidity and mortality. Today, it is important to not only treat heart failure itself but also the related comorbidities. Among them, cardiac cachexia is one of the major challenges. It is a complex multifactorial disease with a negative impact on quality of life and prognosis. Therefore, prevention, early recognition and treatment of cardiac cachexia is essential. Recent findings: Cardiac cachexia frequently presents with skeletal as well as heart muscle depletion. Imaging-based diagnostic techniques can help to identify patients with cardiac cachexia and muscle wasting. Several blood biomarkers are available to detect metabolic changes in cardiac cachexia. Summary: Several studies are currently ongoing to better comprehend the underlying pathophysiological mechanisms of cardiac cachexia and to find new treatments. It is essential to diagnose it as early as possible to initiate therapy.